Effect of ACTH on plasma cortisol and on haematological parameters in swine - Adnan, S.; Graves, C. N.; Curtis, S. E. (Persatuan Doktor Veterinar Malaysia, 1985)

(untitled)
Heparinized blood samples were collected via indwelling jugular cannula from three gilts at 0800, 0900, 1000, 1200, 1600 and 2000 hr on days 5 and 6 after cannulation. The gilts were injected i.m. with either 0.9% saline (day 5, control) or ACTH prepared in saline (day 6) immediately after blood sampling at 0800 hr. ACTH treatment resulted in a significant (p <0.01) increase in plasma cortisol level to values corresponding to those observed during stress in swine. Haematological responses to ACTH treatment showed increased total RBC and WBC counts, Hb concentration and PCV. After ACTH treatment the ratio of lymphoctes and neutrophils were reversed, resulting in lymphopenia and neutrophilia. Monocytosis, eosinopenia and basopenia were also observed.